3D Computed Tomography Virtual Intravascular Endoscopy: Clinical Applications in Cardiovascular Disease. - Sun, Zhonghua (Nova Publishers, 2013)
Medical imaging of cardiovascular disease has improved rapidly with faster multislice CT angiography. The ability to visualize 3D reconstructed vascular structures has given clinicians a much better appreciation of the anatomy and the disease process. This book provides an overview of the diagnostic applications of CT virtual intravascular endoscopy (VIE) in cardiovascular disease. It is intended to fill the gap by providing a systematic overview of the diagnostic applications of VIE in cardiovascular disease. This book serves as a comprehensive piece of literature that encompasses all aspects from the technical principles of VIE image generation to diagnostic value and potential pitfalls of VIE in cardiovascular imaging. The primary motion to write this book is to provide an overview of the CT VIE in cardiovascular disease with a focus on the clinical applications and diagnostic value of this unique visualization tool. It is expected that readers, especially clinicians will gain a good understanding of the diagnostic value of CT VIE in the diagnosis of cardiovascular disease, so that their medical practice is enhanced with use of this exciting complementary visualization tool. (publisher website)